Pro-Angiogenetic Effects of Purified Extracts from Helix aspersa during Zebrafish Development - Daniela Zizioli; Andrea Mastinu; Alessia Muscò; Sara Anna Bonini; Dario Finazzi; Rosaria Avisani; Giovanni Battista Kron Morelli; Sergio Pecorelli; Maurizio Memo (Current Issues in Molecular Biology, 2022)
Helix aspersa is a species of land snail belonging to the Helicidae family, widespread in the Mediterranean and continental area up to Northern Europe. In some areas it is appreciated as a food, but is mostly considered a parasite of gardens and cultivated fields. The mucus of Helix aspersa has found multiple applications in the cosmetic and health fields. In the present study, we investigated for the first time the angiogenetic properties of purified extracts from Helix aspersa using a transgenic zebrafish line Tg (kdrl:EGFP). The angiogenesis induced by purified snail extracts was demonstrated by their capability to increase the three well-established parameters of angiogenesis: generation of intersegmental vessels, modeling of caudal venous plexus, and formation of sub-intestinal venous plexus. The effects appeared to be mediated by the vascular endothelial growth factor (VEGF) pathway, being prevented by pretreatment of embryos with the selective VEGF receptor antagonist SU5416, and supported by the increased VEGF mRNA levels found in snail-extract-treated embryos. Insufficient vascular supply is underlined by low VEGF signaling, primarily because of its indispensable role in preventing capillary loss. Our findings might have a pharmacological impact by counteracting VEGF hypofunction and promoting angiogenesis to maintain adequate microvascular and vascular density in normal and suffering tissues and organs.